Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
Let the no. be X and Y
X - Y = (-1)
X + Y = 1
X = (-1)+ Y
X = 1 - y
- 1.+ y = 1 - y
Y + Y = 1 + 1
2y = 2
Y = 1
X = 0
Answer:
x = 0 (first number), y = 1 (second number)
Step-by-step explanation:
x will represent the first number, and y will represent the second.
x - y = -1
x + y = 1
Now, it's time to get y by itself in one equation so that we can substitute.
x - y = -1 (subtract x from both sides)
-y = -1 - x (multiply both sides by -1)
y = x + 1
Plug in x + 1 for y in the second equation.
x + x + 1 = 1 (combine the x with the x)
2x + 1 = 1 (subtract 1 from both sides)
2x = 0 (divide both sides by 2)
x = 0
Since x = 0, we can plug 0 in for x into any equation to solve for y.
0 + y = 1
y = 1
Brainliest, please :)
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.